Variations in the Lipid-Composition of Alfalfa Roots During Colonization with the Arbuscular Mycorrhizal Fungus Glomus Versiforme - Gaspar, Laura (1997)
Fil: Gaspar, Laura. Instituto de Investigaciones Bioquímicas de La Plata (INIBIOLP). Universidad Nacional de La Plata; Argentina